Pengaruh Customer Knowledge, Faktor Organisasi Dan Infrastruktur Knowledge Management Terhadap Implementasi Customer Relation Management - Pertiwi, Asri (LPPM of STIMIK ESQ, 2015)
In the 21st century, the awareness that customers have a value and that customers prefer quality rather than price, began increasing. The impact is, company started to focus on customer relationships to retain customers and create a loyal customer. In building relationship with customers, some companies use CRM tools to combine customer data with managers. But the conversion process of customer data into customer knowledge is not easy. One of approach to solve the problems of implementation of CRM is to apply knowledge management into the customer relation management in order to not only for maximizing operational area but also streamline the strategic areas through CRM to gain and share knowledge about customer. Successful implementation of CRM is not only supported by the integration of customer knowledge and knowledge management but also need supporting from the organization.